Consent in dentistry: ethical and deontological issues. Issue 1 (12th October 2012) - Conti, Adelaide; Delbon, Paola; Laffranchi, Laura; Paganelli, Corrado
Abstract : In Italy, consent for health treatment, aside from being an ethical and deontological obligation, constitutes an essential requirement for any medical treatment according to articles 13 and 32 of the National Constitution and also in accordance with the Council of Europe's 'Convention on Human Rights and Biomedicine'. An essential requirement for the validity of consent is that clear, exhaustive and adequate information be provided to the patient himself: the practice of informed consent is a communicative relationship in which the patient can express doubts, perplexities and clarification requests to the dentist. Furthermore, dental treatment has specific peculiarities: the relationship between dentistry and aesthetics, the concomitant presence of pathologies requiring different treatments, the elongated care process and the establishment of a trustworthy relationship and familiarity with the patient represent important aspects in the configuration of the dentist-patient relationship and in the process of acquiring informed consent. The dentist must offer correct information on diagnosis, prognosis, the therapeutic perspective and the likely consequences of therapy, alternative therapy and refusal of therapy, as well as eventual commitments for the period after treatment. Particular consideration must be given to minors and patients of unsound mind: the dentist's approach to these patients needs to be clear and appropriate to the person's age and understanding ability, even if the decisional power for sanitary treatment may be in the hands of a third person.